ANALYZING THE DIMENSION OF BRAND EQUITY TOWARD REPURCHASE INTENTION OF KOPI KULO IN MANADO - Kalesaran, Maesa R.; Lapian, Joyce S.L.H.V.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Enjoying coffee now has become a lifestyle. Unlike before, coffee now is consumed at various times by various walks of life, therefore many coffee brands are starting to emerge. Kopi Kulo is one of the brands that enter Manado that provides ready-to-drink coffee, and this research uses Kopi Kulo as a reference for its brand. A good brand preference can provide loyal customers. This goal of the research is to strengthen the company’s reputation so that it will resist attacks from competitiors. By using quantitative method, this study uses three independent variables of brand equity, namely Brand Awareness, Brand Image, and Brand Loyalty, and Repurchase Intention as the dependent variable. Through a questionnaire distributed to one hundred people who had consumed Kopi Kulo more than once, it was found that the three independent variables had an influence on the dependent variable but Brand Awareness as one of the independent variables did not have a significant effect on Repurchase Intention. And significantly Brand Image and Brand Loyalty partially influence the intention to repurchase. Based on the results of this study, the recommendation for Kopi Kulo is to improve their social media marketing strategy to attract customers, and Kopi Kulo needs to post interesting promotions on social media for their customers.Keywords: brand equity